2020
DOI: 10.1136/jclinpath-2020-206494
|View full text |Cite
|
Sign up to set email alerts
|

NGAL and SMAD1 gene expression in the early detection of diabetic nephropathy by liquid biopsy

Abstract: IntroductionDiabetic nephropathy (DN) is a disease that progresses with the slow and progressive decline of the glomerular filtration rate (GFR); the installation of this pathology is silent and one of the major causes of death in patients with diabetes.AimsTo identify new molecular biomarkers for early identification of the onset of DN in patients with type II diabetes mellitus (DM2). We studied the expression profile of the genes; suppressor of mothers against decapentaplegic type 1 (SMAD1), neutrophil gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…Peripheral blood NGAL gene expression was increased in patients with type 2 DM compared with healthy individuals (type 2 DM 0.09758 ± 0.1914* 2 −ΔCq vs CTL 0.02293 ± 0.04578). 25 The results showed a positive correlation between serum NGAL and HbA1c in T2DM patients with normoalbuminuria, 23 which is in agreement with DyabAllawi et al 2017 who showed significant correlation between serum NGAL and HbA1c % (r = 0.394, p = 0.03) 24…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Peripheral blood NGAL gene expression was increased in patients with type 2 DM compared with healthy individuals (type 2 DM 0.09758 ± 0.1914* 2 −ΔCq vs CTL 0.02293 ± 0.04578). 25 The results showed a positive correlation between serum NGAL and HbA1c in T2DM patients with normoalbuminuria, 23 which is in agreement with DyabAllawi et al 2017 who showed significant correlation between serum NGAL and HbA1c % (r = 0.394, p = 0.03) 24…”
Section: Resultssupporting
confidence: 80%
“…They suggest the potential use of SMAD1 gene expression in peripheral blood and urine samples as early biomarkers of DN. 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the clinical diagnosis of DN mainly depends on the elevated urinary albumin excretion and reduced eGFR in the absence of other primary causes of kidney damage, lacking high sensitivity and specificity indicators to reflect the renal blood oxygen levels. A growing number of studies have focused on the biomarkers for early diagnosis of DN, which include (I) certain urinary microRNAs such as microRNA-210 and microRNA-34a (7), urinary kidney injury molecule 1 (KIM-1) and Chitinase-3-like protein 1 (YKL-40) (8), urinary E-cadherin ( 9); (II) serum galectin-3 and growth differentiation factor-15 (GDF-15) (10), serum pregnenolone sulfate, ganglioside GA1, phosphatidyl glycerol and all-trans-Carophyll yellow tested by direct flow through mass spectrometry (11); (III) suppressor of mothers against decapentaplegic type 1 (SMAD1) and neutrophil gelatinase-associated lipocalin (NGAL) gene expression in peripheral blood and urine samples (12). However, renal biopsy is still the gold standard to diagnose diabetic nephropathy.…”
Section: Diabetic Nephropathy (Dn)mentioning
confidence: 99%
“…A number of studies have studied the relationship between abnormal expression of different genes and DN progression. For instance, Veiga et al 14 presented the eccentric expressions of NGAL and SMAD1 genes in blood and urine samples in DN patients by liquid biopsy, suggesting the potentials of NGAL and SMAD1 in DN early diagnosis. Gong et al 15 claimed that KLF4 serves as a protective regulator in DN by activating podocyte autophagy.…”
Section: Introductionmentioning
confidence: 99%